Improved energy balance theory applied to roadway support design in deep mining. (9th May 2018) - Wang, Chunlai; Liu, Lu; Elmo, Davide; Shi, Feng; Gao, Ansen; Ni, Pengpeng; Zhang, Binchuan
Abstract: Deep mining excavations are challenging, especially because roadways are subject to increasingly high stresses and large deformations. In particular, effective support patterns are required to prevent failures associated with deep mining. The conventional energy balance theory cannot be directly applied for roadway support design in deep mining. In this paper, assumptions were made to improve the energy balance theory, where a semi-circular roof roadway experiencing geostatic stresses was analyzed under plane strain conditions and its failure was identified by the Hoek–Brown failure criterion. An improved energy balance theory was proposed to solve the problem, where the released energy in the plastic zone of the roadway was supposed to be less than the maximum absorbed energy of the supporting structures. The optimized roadway support pattern and parameters for deep mining were then determined through elastic mechanics and complex analysis. The efficacy of the proposed method was evaluated using case histories of roadway support design at the Da'anshan coal mine and the Jinchuan III nickel mine.